SISTEM PERSAMAAN LINEAR FUZZY - Noeranita, Beta (MATEMATIKA, 2008)
Let AU = V be fuzzy system of linear equations. The fuzzy system of linear equations consist of n variables and n equations.We rearrange the fuzzy system of linear equations became 2n variables and 2n equations. The new system was devoted by BX* = V*. In this paper, we show that solution of BX* = V* can be used to find AU = VÂ fuzzy system of linear equations, whenever B-1 is non-negative. Â